Influence of reducing heat treatment on the structural and magnetic properties of MnO:ZnO ceramics - Lage, V.M. Almeida; da Silva, R. T.; Mesquita, A. [UNESP]; de Godoy, M. P.F.; Gratens, X.; Chitta, V. A.; de Carvalho, H. B. (Elsevier, 2021)
Polycrystalline MnO:ZnO bulk ceramics with a Mn proportion of 6, 11, 17 and 22 at% are prepared through a solid-state reaction and subjected to a heat treatment in a reducing atmosphere (Ar (95%) and H2 (5%)). The samples are studied with particular emphasis on their composition and structural and magnetic properties. A detailed microstructural and chemical analysis confirms the Mn doping of the wurtzite ZnO structure mainly at the surface of the ZnO grains. For the samples with higher Mn proportions, the secondary phases ZnMn2O4 and Mn1−xZnxO (Zn-doped MnO) are detected for the as-prepared and heat-treated samples, respectively. The structural change of the secondary phases under heat treatment, from ZnMn2O4 to Mn1−xZnxO, confirms the effectiveness of the heat treatment in reducing the valence of the Mn ions and in the formation of oxygen vacancies into the system. In spite of the induced defects, the magnetic analysis presents only a paramagnetic behavior with an antiferromagnetic coupling between the Mn ions. In the context of the bound magnetic polaron theory, it is concluded that oxygen vacancies are not the necessary defect to promote the desired ferromagnetic order at room temperature.
Keywords: Defect engineering; Multifunctionality; Spintronics; Zinc oxide